UMP collaborates with 3 industries to improve graduate competitiveness - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
KUALA LUMPUR, 26 June 2022 - Universiti Malaysia Pahang (UMP) collaboration with three industries involving Celcom AXIATA Berhad, Gebeng Glove Industries Sdn. Bhd. and Akar Indah Engineering Sdn. Bhd. focuses on areas related to entrepreneurship, human capital development and research development to improve future graduate employability.